The Effectiveness of Learning Management Before, During and After Covid-19 - Halwati Halwati (Indonesian Journal of Education (INJOE), 2021)
Learning is essentially a business, a process of change that occurs in individuals as a result of experience or the result of interaction with the environment. Effective learning is a teaching and learning process that is not only focused on the results achieved by students, but how an effective learning process is able to provide good understanding, intelligence, perseverance, opportunity and quality and can provide behavior change and apply it in their lives. In answering the phenomenon of learning effectiveness, the writer uses the library method to collect the material needed by the author in completing it. At this time the Covid-19 virus spread which resulted in the learning system undergoing many changes. The learning system that was originally implemented face-to-face or directly must be changed to an online learning system, in which teachers and students learn remotely using the internet. After the pandemic began to subside, the learning system underwent a change again by using                  face-to-face learning on a limited basis